Environmental Kuznets Curve Theory on Environmental Degradation in ASEAN-5 - Ramadhanti Ramadhanti; Azwardi Azwardi; Muhammad Subardin (Universitas KH. Abdul Chalim Mojokerto, 2026)
The decline in environmental quality due to increasing greenhouse gas emissions is now a crucial challenge amidst the rapid industrialization of the Southeast Asian region. This study aims to empirically test the validity of the Environmental Kuznets Curve (EKC) hypothesis and analyze the effects of economic growth, energy consumption, population, and urbanization on CO₂ carbon dioxide emissions in the five founding countries of ASEAN (ASEAN-5), namely Indonesia, Malaysia, Thailand, the Philippines, and Singapore. Using secondary time series data from 2009 to 2023, the analysis was conducted using a panel data regression approach through the Fixed Effect Model (FEM) method corrected using White diagonal standard errors & covariance estimates to overcome heteroscedasticity and autocorrelation bias. The estimation results show that the economic growth variable (GDP) has a positive and significant effect, while the quadratic economic growth (GDP2) has a negative and significant effect on CO₂ emissions. This combination confirms the validity of the EKC hypothesis which forms the characteristics of an inverted U-Shape curve in the ASEAN-5 region. Through mathematical calculations, it was found that the turning point for the regional economy was at a nominal GDP per capita of 69,117.65 USD. In the control variable, total population (POP) was shown to have a positive and highly significant influence as the main driver of increasing carbon emissions. In contrast, the variables of energy consumption (energy use) and urbanization rate did not show a significant influence on CO₂ emissions at the regional aggregate level during the observation period. The results of this study indicate that most developing countries in the ASEAN-5 are still on the left side of the ecological curve (below the turning point threshold). Therefore, clean energy transition policy interventions, strict carbon exchange regulations, and eco-city spatial planning are needed to reduce emissions without sacrificing the rate of macroeconomic growth.